The Development of an Interwar Suburb: Kingsway Park, Etobicoke - Paterson, Ross (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1985)
An examination of planned suburbanisation is provided in this study through a discussion of the activities of the Home Smith and Company, and in particular, by an examination of the development and building of one of the Company's premier subdivisions, Kingsway Park. The study presents further evidence that the inter-war period encompassed a pivotal period in the evolving city-building process, bridging the transition between the fragmentary system employed in building the Victorian suburbs and the highly integrated land development process in place today.